An overview of the prevalence of micro- and nanoplastics in the Southern African development community: a potential risk to environmental and public health - Babalwa Gqomfa; Seteno Karabo Ntwampe; Boredi Silas Chidi; Thabang Maphanga; Cynthia Dlangamandla (Discover Environment)
Abstract Rapid urbanisation, industrial development, and inadequate solid waste management systems, finances, and even legal frameworks have exacerbated Southern African Development Community (SADC) plastic waste and micro and nanoplastics (MNPs) proliferation, raising serious public health and ecological concerns. There is scant information on the occurrence of MNPs in the SADC, especially in rivers, streams, wetlands, and lakes which are vital as freshwater sources and food producers. This systematic review analyses the occurrence of MNPs within the water bodies of SADC. The literature, which included 84 published papers, was collected through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology with additional literature (n = 39) that confirmed MNPs' presence in these ecosystems. Some prominent examples of water bodies that have shown the prevalence of MNPs are Namibia’s Main River and South Africa's Crocodile and Vaal Rivers. Pollution caused by urban runoff and degradation of plastic waste stemming from industrial activities is critically damaging to the environment, particularly the soil, water, food web, and biodiversity of the region. Overall, there is a dearth of research directed towards investigating the occurrence of MNPs in SADC countries with most studies concentrating on bulk plastic waste, underscoring the need for public awareness and stricter regulations on plastic production and waste to mitigate MNP pollution.